2017
DOI: 10.1111/1755-5922.12306
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine reverses hyperhomocysteinemia‐induced vascular dysfunction via PKA‐dependent mechanisms

Abstract: This study shows that alamandine is effective in reversing HHcy-induced vascular dysfunction, possibly through the PKA signaling pathway via MrgD. Our results indicate a therapeutic potential of alamandine in reversing the detrimental effects of HHcy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Likewise, alamandine has anti-hypertensive properties, enhances vasodilation and reverses endothelial dysfunction in spontaneous hypertensive rats and homocysteine-induced endothelial dysfunction rabbits [12,72]. Hence, as Ang (1-7) can reverse the negative effects of Ang II on endothelial dysfunction, superoxide production, as well as lowering Ang II-induced atherosclerotic lesions and plaque formation, further studies with alamandine could show similar findings, and together these heptapeptides could reduce the progression of CVD.…”
Section: Ang (1-7) and Mas Receptor Counterbalance The Effects Of Angmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, alamandine has anti-hypertensive properties, enhances vasodilation and reverses endothelial dysfunction in spontaneous hypertensive rats and homocysteine-induced endothelial dysfunction rabbits [12,72]. Hence, as Ang (1-7) can reverse the negative effects of Ang II on endothelial dysfunction, superoxide production, as well as lowering Ang II-induced atherosclerotic lesions and plaque formation, further studies with alamandine could show similar findings, and together these heptapeptides could reduce the progression of CVD.…”
Section: Ang (1-7) and Mas Receptor Counterbalance The Effects Of Angmentioning
confidence: 97%
“…To further understand the similar roles amongst Ang (1-7) and alamandine, we recently demonstrated that ex vivo treatment of alamandine to isolated rabbit aortas reversed homocysteine-induced endothelial dysfunction by activating the PKA pathway for vasorelaxation [72]. Although we demonstrated the presence of MrgD receptor using immunohistochemistry in another study [22], others have shown that CHO cells transfected with MrgD receptor and cultured with alamandine, high levels of NO is produced but not in normal CHO cells, suggesting that alamandine binds to MrgD receptor to induce NO production via increasing eNOS activity [12].…”
Section: Alamandine and The Mrgd Receptor: Similarities To Ang (1-7)mentioning
confidence: 99%
“…Using molecular modelling, components of the RAS (especially ACE-I peptides) have been designed and used as anti-hypertensives [59]. More recently, alamandine, a vasoactive peptide of the RAS, was shown to reverse vascular dysfunction via the protein kinase A pathway [60]. Examples of ACE-I include benazepril hydrochloride, captopril, perindopril, enalapril maleate and of ARBs include candesartan, irbesartan, losartan, valsartan.…”
Section: Regulation Of Blood Pressurementioning
confidence: 99%
“…Furthermore, the reduction of blood pressure observed by ARBs is claimed to be due to the reduction in ANGII/AT1R signaling, yet circulating ANGII is increased nearly 5-fold [31] and the kidney plays a significant role in hypertension in rat [32]. We propose that blockade of the AT1 receptor could reveal other vasodilative effects in the vasculature, by enhancing the vasodilatory peptides of RAS, such as alamandine [33,34] in kidney blood vessels. Alamandine, a novel heptapeptide of the RAS, has been demonstrated to enhance acetylcholine (ACh)mediated vasodilation in New Zealand white rabbits in vitro [35] and antihypertensive effects in spontaneously hypertensive rats after oral administration [36].…”
Section: Introductionmentioning
confidence: 88%